Integrating Marketing Concepts in Competitive Decision Making — A Case Study - Manion, Michael T.; Akowuah, Lovina (Journal of Marketing Development and Competitiveness, 2020)
Students experienced applying Marketing concepts while making decisions in multiple disciplines (including Marketing, R&D, and Production) in a Competitive Decision-Making course. Marketing students competed to achieve desired performance outcomes (such as, Market Share, ROS, and Cumulative Profit) in a realistic business simulation. Marketing students applied an array of ten traditional Marketing concepts in this experiential course: 1. Market Scaling; 2. Market Segmentation; 3. Product Pricing; 4. Product Ageing; 5. Product Positioning; 6. Product Reliability; 7. Promotions Budgets and Media Selection; 8. Sales Staffing and Channel Selection; 9. Market Research; and 10. Sales Forecasting.